Given the function f(x) = 2x^3 and the function g(x) = x+log x.

We need to find f(g(10)).

First we will determine f(g(x)).

f(g(x) = f ( x+ log x).

Substitute with x= ( x+ log x ) into f(x).

= 2(x+log x) ^3

Now to find f(g(10)) we will substitute with x = 10

==> f(g(10)) = 2 ( 10 + log10)^3

But we know that log 10 = 1

==> f(g(10)) = 2(10 + 1)^3

= 2(11)^3

= 2*1331

= 2662

==**> f(g(10)) = 2662**

We are given f(x) = 2x^3 and g(x) = x + log x and we have to find f(g(10)

Now f(x) = 2x^3

g(x) = x + log x

f (g(x) = f ( x + log x)

=> 2* ( x + log x)^3

To find f(g(10) we have to substitute x for 10 in

f(g(x)) = 2* ( x + log x)^3

=> 2*( 10 + log 10)^3

=> 2* ( 10 + 1)^3

=> 2* 11^3

=> 2*1331

=> 2662

**Therefore f(g(10) = 2662**

f(x) = 2x^3 and g(x0 = x+logx. To find f(g(10).

Since f(x) = 2x^3, we get f(g(x)) by replacing x by g(x) in 2x^3.

Therefore f(g(x)) = 2(x+logx)^3.

To find f(g(10)) , we put x= 10 in f(g(x)) .

Therefore f(g(10) ) = 2(10+log10)^3. But log 10 = 1.

Therefore f(g(10)) = 2(10+1)^3 = 2662.

Therefore f(g(x)) = 2 (x+logx)^3. andf(g(10)) = 2662.